Assessment of the seismic behavior of reinforced concrete elements affected by corrosion: An objective comparison between quasi-static and dynamic tests. (May 2022) - Lejouad, C.; Richard, B.; Mongabure, P.; Capdevielle, S.; Ragueneau, F.
Abstract: Corrosion of steel reinforcement is one of the most widespread pathologies that leads to a loss of structural performance of reinforced concrete (RC) members. Thus, understanding the mechanical consequences of this pathology is of great importance. In the past decades, many studies have been performed to assess the influence of the reinforcement corrosion on the quasi-static behavior of RC structures. However, few investigations have been carried out to characterize the corroded structural dynamic behavior under extreme loading. In this study, the case of the earthquake loading is investigated. The objective is to provide the scientific community with reference experimental data to assess the influence of corrosion on the dynamic properties of structural members. These experimental data are very valuable when calibrating numerical models aiming to determine some significant engineering demand parameters (EDP) such as the bearing capacity, the ductility and the dissipation ability. Furthermore, the relevance of the use of quasi-static tests in predicting the seismic behavior of corroded RC elements is assessed. To reach this goal, an experimental campaign is conducted on large-scale RC beams. The corroded and non-corroded beams are subjected to a four-point bending test and to dynamic loads on the AZALEE shaking table (keeping the same loadings and boundary conditions). In this paper, a detailed description of the experimental campaign is presented. Then, the results are exposed, showing the influence of the corrosion rate on the bearing capacity, hysteretic response, ductility offer, eigenfrequencies and damping ratios.